Microtremor Data Processing and Interpretation: A Case Studi on Area Damaged by Yogyakarta 2006 Earthquake - Purnama, Aditya Yoga; Nurhanafi, Kholis; Nurcahya, Budi Eka; Amalia, Ayu Fitri (Proceeding International Conference on Religion, Science and Education, 2022)
The MATLAB was applied for processing microtremor data in the Yogyakarta area damaged by the 2006 earthquake. This study aimed to process and interpret microtremor data using Matlab software. A total of 7 microtremor data were processed using the HVSR (Horizontal-to-Vertical Spectral Ratio) method. Measurements were made directly at points damaged by the 2006 Yogyakarta earthquake, namely the ISI, STIE Kerjasama, BPKP DIY, Lippo Plaza, Amongrogo, Purawisata, and Mount Ireng for comparison. This paper has succeeded in processing microtremor data using the Matlab programming language. The results of processing microtremor data between Geopsy software and MatLab are not much different. According to the research result, a lot of damage occurred in the sediment area of Yogyakarta compared to the Wonosari hills that had a more solid layer. The amplification factor indicates building damages due to the Yogyakarta earthquake.